EFEKTIVITAS BERKUMUR LARUTAN INFUSUM DAUN GUAVA (Psidium Guajava Linn) DALAM MENURUNKAN INDEKS PLAK - Tika Fauzara Ikhsan; Yustini Allioes; Kosno Suprianto (Andalas Dental Journal, 2017)
Plaque is a sticky deposit, consists of bacteria and it’s products in the form of biofilm that breed in a matrix on the surface of the tooth. Plaque can control chemically by using mouthwash. The infuse solution of guava leaf (Psidium guajava Linn) can be used as a herbal mouthwash. Antibacterial potency from the flavonoid in guava leaf can inhibit the growth of Streptococcus mutans and glucosyltransferase enzyme activity. The purpose of this studi is to determining the effectiveness of gargling guava leaf (Psidium guajava Linn) infuse solution in reducing plaque index. This study was conducted with pre-test post-test control group design to 32 students of Dentistry Faculty of Andalas University as respondents in two days. The first day, 32 respondents gargled with aquades as a control group and the second day, 32 respondents gargled with infuse solution of guava leaf (Psidium guajava Linn) with 80% concentration as the case group. The plaque index was observed with modified plaque index Turesky-Gilmore-Glicman of Quigley-Hein. Result of the study is there is difference in the reduction of plaque index between the control group and the case group significantly (p <0.05), which the plaque index is lower in the case group than the control group. Conclusion of this study concluded that the infuse solution of guava leaf (Psidium guajava Linn) was effective in decreasing plaque index. Keywords:Infuse solution of Guava leaf (Psidium guajava Linn), plaque index